Observation Unit Management of Older Adults with Rib Fractures: A Case Series - Phillip D Jenkins; Elizabeth K Crawford Rowe; Colin Gershon; Mackenzie Cook; John Marshall (Clinical Practice and Cases in Emergency Medicine, 2026)
Introduction: Rib fractures in older adults carry high morbidity and mortality, leading many hospitals to admit patients based on age alone. The Rib Injury Guidelines (RIG) offer a triage system; under RIG 2, patients are typically admitted to inpatient care. Case Series: This study evaluated whether older adults categorized as RIG 2 solely due to age could be safely managed in an emergency department observation unit. We conducted a 14-month case series at an academic trauma center, reviewing 23 patients 60 years and older with rib fractures. Twenty met RIG 2 criteria, including those later admitted for nontrauma reasons. The mean observation stay was 26.6 hours, and the total hospital stay was 1.8 days. Seventeen patients (85%) were discharged directly from observation, three (15%) were admitted to medicine, and none returned within 72 hours. Conclusion: Carefully selected older adults with rib fractures may be safely managed in observation units, optimizing resource utilization and patient safety.